Decentralization and health in the Philippines: A systematic review of empirical evidences - Michael R. M. Abrigo; Zhandra C. Tam; Danica Aisa P. Ortiz (Philippine Institute for Development Studies (PIDS), 2017)
This study provides a systematic review and summary of the extant knowledge on the impacts of decentralization on health in the Philippines. Despite the country's twenty-five years of experience in decentralization, little is known about the topic. Overall, our survey shows that the existing scholarship on the impact of decentralization on health in the country is characteristically thin and with varying degree of methodological rigor. The limited available evidences point to some indication of positive impacts of decentralization on increasing government health expenditures and on improving health outcomes.
Keywords: 330; Decentralization; Health; Philippines